Geology Of Tanjung Medan ,Rokan IV Koto , Rokan Hulu District, Riau Province - Budi Prayitno; Susilo Susilo (UIR PRESS, 2018)
The Administrative of research area has been in Tanjung Medan, Rokan IV Koto, Rokan Hulu, Riau Province and geographically located at 0 ° 37 '28.488